Diagnosis Kesulitan Siswa dalam Menyelesaikan Masalah Geometri-PISA Melalui Pemetaan Kognitif dan Upaya Mengatasinya dengan Scaffolding - Agung Prasetyo Abadi; Subanji Subanji; Tjang Daniel Chandra (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2017)
This study, thus, has unveiled the students’ difficulties in solving PISA-geometry problems and some efforts to face them through scaffolding. This research use qualitative approach. The student were given the problems of PISA-geometry then 6 student were choosen as the subject of study. The data were got from the results of the students’ work PISA-geometry was conducted, involving: understanding of problems, associating the problems with the concept having been taught especially Pythagorean theorem, calculating multiplication of decimals, simplifying the problems, elaborating the skecth, and deciding strategies of problem solving. Scaffolding conducted by researches is refers to scaffolding Anghilari level 2 (explaining, reviewing and restructuring).